Analyzing online marketing for contemporary snacks through Instagram using SIR Model / Nur Syazwani Atikah Mohd Hilmi and Noorzila Sharif - Mohd Hilmi, Nur Syazwani Atikah; Sharif, Noorzila (UiTM Cawangan Perlis, 2022)
During the implementation of the Movement Control Order (MCO), e-marketing became a favourable solution for sellers to interact with customers at home. Today, even though the MCO is no longer in existence, online shopping behaviours have become a new norm because of a long-term impact on the interactions between seller and buyer. Since the number of online marketing is growing, sellers must understand the concept of viral marketing that suits their products. This study analyses the virality of contemporary snack marketing on the Instagram platform using the Susceptible-Infected-Recovery (SIR) model. It is essential for sellers or marketers who want to see how users react to various types of posting. It also makes it easier for customers to get the information from the postings. The parameters used in this model are the number of followers, number of reached users, and number of homepage visits. Data are collected from 14 July 2021 until 11 October 2021 at an Instagram account that promotes a type of chocolate-in-jar snack. There are three types of posting that the admin of the Instagram account frequently uses to gain customer interaction, which are Feed, Reels, and Stories. The most viral posting from each type is observed. The results reveal among the viral posts, Reels recorded the highest virality posted on 11 September 2021 (Saturday).